Profile of Students' Mathematical Problem Solving Ability in the High Category in terms of Learning Motivation and Numeracy Ability - Ratnasari Meliana; Hanifah Nurus Sopiany (JPMI (Jurnal Pendidikan Matematika Indonesia), 2023)
This study aims to describe the profile of students' mathematical problem solving abilities in the high category in terms of learning motivation and numeracy abilities. This type of research is descriptive with a qualitative approach. The subjects of this study were class IX students of SMP PUI YATSHI in the odd semester of the 2022/2023 academic year. The subjects of this study were determined by purposive sampling by selecting one student from each category of mathematical problem solving ability test results consisting of high, medium, and low ability categories. based on students who have learning motivation and high, medium, and low numeracy abilities. However, what will be explained in this study is only subjects with high problem-solving abilities based on learning motivation and high numeracy abilities. Data collection techniques used were mathematical problem solving ability test instruments, students' numeracy ability test instruments, interviews, and data triangulation. Data analysis techniques in this study are data reduction, data presentation and conclusion. The results of this study are to describe the profile of students' mathematical problem-solving abilities in the high category in terms of learning motivation and numeracy abilities, namely students' mathematical problem-solving abilities in the high category with high learning motivation and students' numeracy abilities, so the subject is able to: (1) understand the problem, namely being able to determine what is known and asked from the problem; (2) make a problem solving strategy plan, namely being able to determine the formula or solution model used in solving the problem; (3) carrying out a strategic problem solving plan, namely being able to perform calculations from formulas that have been used correctly and correctly; (4) re-examining the results obtained, namely being able to determine the final conclusion and write the final answer correctly.